Contextual variations in perceived social values of ecosystem services of urban parks: A comparative study of China and Australia. (January 2017) - Swapan, Mohammad Shahidul Hasan; Iftekhar, Md Sayed; Li, Xiyuan
Abstract: Parks are an integral part of urban environment which provide a range of ecosystem services. While a great deal of efforts has been invested to investigate monetary and biophysical benefits of natural ecosystems, very few studies have explored socio-ecological values of urban parks. Comparative studies of ecosystem services from urban parks between multiple countries are even rarer. To address this research gap, we have compared users' perceptions of ecosystem services of two major urban parks in China (Dufu Cottage, Chengdu) and in Australia (Kings Park, Perth). Using an ecosystem services framework, we explored three key questions: (i) which ecosystem services are perceived to be most important? (ii) what are the trends of ecosystem services provided by the park? and (iii) which demographic and socio-economic factors influence users' perceptions most? We observed that there is no substantial difference in users' perceptions (in terms of importance and trend) of ecosystem services between two countries, except for microclimate service. Respondents in Dufu Cottage perceived microclimate as the most important service while in Kings Park, a number of services (e.g., aesthetic, habitat and recreational) received almost equal importance. Almost two-thirds of the respondents have perceived an increased level ecosystem services over the last five years. Various socio-demographic factors, such as gender, age, income level and frequency of visits influenced users' perceptions most significantly. These results have critical implications in designing more environmentally sensitive as well as user-oriented urban parks. Highlights: Very few studies have explored socio-ecological values of urban parks. We have conducted a cross-national comparative studies of environmental services provided by urban parks. There are little contextual differences of valuation of ecosystem services. Gender, age and frequency of visits influenced users' valuation most significantly.